K18-hACE2 mice develop respiratory disease resembling severe COVID-19 - Yinda, Claude Kwe; Port, Julia R.; Bushmaker, Trenton; Offei Owusu, Irene; Purushotham, Jyothi N.; Avanzato, Victoria A.; Fischer, Robert J.; Schulz, Jonathan E.; Holbrook, Myndi G.; Hebner, Madison J.; Rosenke, Rebecca; Thomas, Tina; et al. (PLoS pathogens, 2021)
SARS-CoV-2 emerged in late 2019 and resulted in the ongoing COVID-19 pandemic. Several animal models have been rapidly developed that recapitulate the asymptomatic to moderate disease spectrum. Now, there is a direct need for additional small animal models to study the pathogenesis of severe COVID-19 and for fast-tracked medical countermeasure development. Here, we show that transgenic mice expressing the human SARS-CoV-2 receptor (angiotensin-converting enzyme 2 [hACE2]) under a cytokeratin 18 promoter (K18) are susceptible to SARS-CoV-2 and that infection resulted in a dose-dependent lethal disease course. After inoculation with either 10 4 TCID 50 or 10 5 TCID 50 , the SARS-CoV-2 infection resulted in rapid weight loss in both groups and uniform lethality in the 10 5 TCID 50 group. High levels of viral RNA shedding were observed from the upper and lower respiratory tract and intermittent shedding was observed from the intestinal tract. Inoculation with SARS-CoV-2 resulted in upper and lower respiratory tract infection with high infectious virus titers in nasal turbinates, trachea and lungs. The observed interstitial pneumonia and pulmonary pathology, with SARS-CoV-2 replication evident in pneumocytes, were similar to that reported in severe cases of COVID-19. SARS-CoV-2 infection resulted in macrophage and lymphocyte infiltration in the lungs and upregulation of Th1 and proinflammatory cytokines/chemokines. Extrapulmonary replication of SARS-CoV-2 was observed in the cerebral cortex and hippocampus of several animals at 7 DPI but not at 3 DPI. The rapid inflammatory response and observed pathology bears resemblance to COVID-19. Additionally, we demonstrate that a mild disease course can be simulated by low dose infection with 10 2 TCID 50 SARS-CoV-2, resulting in minimal clinical manifestation and near uniform survival. Taken together, these data support future application of this model to studies of pathogenesis and medical countermeasure development.